Class III glands in the abdomen of Meliponini - Cruz-Landim, Carminda da [UNESP]; Abdalla, Fábio Camargo [UNESP]; Gracioli-Vitti, L. F. (Edp Sciences S A, 2006)
Class III tegumentar glands were studied in workers, as well as in queens and males when available, of 56 Meliponini species. The presence and development of these glands varies widely among and within species. However, the queen typically has more glands than do workers, and males rarely have any. Gland development in workers was evaluated by counting and determining the size of cells in histological sections. Laying queens were found to have more active gland cells than did virgins. Cell numbers and cell ultrastructure differed among glands similarly located in workers, queens and males. Cell size and ultrastructure also varied from tergite to tergite. In conclusion, since it is likely that most of them produce pheromones, the wide variability in these glands suggests that they are important to social interaction.
Keywords: stingless bee; tergal gland; histology; ultrastructure; worker; queen; male